2005
DOI: 10.1108/02686900510611249
|View full text |Cite
|
Sign up to set email alerts
|

The development of quality management accounting practices in China

Abstract: PurposeThe concept of the market economy is gaining ground in China. So also, with the growth of international business partnerships and collaboration with the West, is the significance of management accounting. The purpose of this paper is to provide some background for the development of management accounting practices in China.Design/methodology/approachAs enterprises gain more autonomy, management accounting techniques such as capital budgeting, cost of capital concept, just‐in‐time inventory, inventory mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 32 publications
3
14
0
Order By: Relevance
“…Yet, there is no extensive research in any of these countries (including Europe), apart from China. (Islam & Kantor, 2005) investigated the development of quality management accounting practices in China (a review of the literature based on MA practices in selected Asian countries was made also by (Sulaiman et al, 2004). According to the authors, changes in the way enterprises are run in China have required more management information, and have consequently forced the development of MAS.…”
Section: Literature Review Management Accounting (Ma) In Transition Amentioning
confidence: 99%
“…Yet, there is no extensive research in any of these countries (including Europe), apart from China. (Islam & Kantor, 2005) investigated the development of quality management accounting practices in China (a review of the literature based on MA practices in selected Asian countries was made also by (Sulaiman et al, 2004). According to the authors, changes in the way enterprises are run in China have required more management information, and have consequently forced the development of MAS.…”
Section: Literature Review Management Accounting (Ma) In Transition Amentioning
confidence: 99%
“…For example research by Scarbrough, Nanni, & Sakurai, 1991;Bright, Davies, Downes, & Sweeting, 1992;Drury, Braund, Osborne, & Tayles, 1993;Anderson & Rohde, 1994;Innes & Mitchell, 1995Chenhall & Langfield-Smith, 1998Abdel-Kader & Luther, 2006 focused on the use of management accounting among large firms in the developed countries. Whereby a substantial body of research investigating current management accounting practices in large organizations from developing countries was conducted by Ghosh & Kai Chan, 1997;Joshi, 2001;Szychta, 2002;Islam & Kantor, 2005;Wu, Boateng, & Drury, 2007;El-Ebaishi, Karbhari, & Naser, 2003;Van Triest & Elshahat, 2007;Frezatti, 2007;Leftesi, 2008;and Nimtrakoon, 2009. Therefore the paucity of research into the use of management accounting practices among SMEs motivates this research.…”
Section: Introductionmentioning
confidence: 99%
“…Chinese nationals are less open in knowledge sharing, which is consistent with culture-based expectations (Chow, Deng, and Ho 2000). It has been suggested that national culture and traditional Chinese business practices have a negative influence on efforts for information dissemination and development of management accounting practices (Islam and Kantor 2005). Tsui (2001) examined the impact of culture on the behavior and attitudes of managers in budgetary participation.…”
Section: Management Accountingmentioning
confidence: 75%